Respect families’ right to commemorate loved ones killed during uprising without reprisals on one-year anniversary - Amnesty International (Amnesty International, 2023)
In new research, Amnesty International details how the Iranian authorities have been subjecting victims’ families to arbitrary arrest and detention, imposing cruel restrictions on peaceful gatherings at grave sites, and destroying victims’ gravestones.
Iran, Islamic Republic of
Keywords: 2023-08 August